Polymorphisms of the gene encoding Kit ligand are associated with bronchopulmonary dysplasia. Issue 3 (9th March 2014) - Huusko, Johanna M.; Mahlman, Mari; Karjalainen, Minna K.; Kaukola, Tuula; Haataja, Ritva; Marttila, Riitta; Toldi, Gergely; Szabó, Miklós; Kingsmore, Stephen F.; Rämet, Mika; Lavoie, Pascal M.; Hallman, Mikko; et al.
Summary Bronchopulmonary dysplasia (BPD) is a chronic inflammatory lung disease that affects infants born preterm. Family studies indicate that BPD has a significant genetic component. Rationale: We assessed the gene encoding Kit ligand (KITLG) as a candidate for genetic predisposition to moderate‐to‐severe BPD (controls were infants with no or mild BPD). Study design: Eight KITLG‐tagging single nucleotide polymorphisms (SNPs) were analyzed in cohorts of very preterm infants originating from northern Finland (56 cases and 197 controls), southern Finland (n = 59 + 52), and Canada (n = 58 + 68). Additional replication populations included infants born in Finland (n = 41 + 241) and Hungary (n = 29 + 40). All infants were of European origin. Results were controlled for risk factors of BPD. Kit ligand concentration in umbilical cord blood, collected from very preterm infants (n = 120), was studied. Results: Six SNPs of KITLG and a haplotype including all eight genotyped SNPs were associated with moderate‐to‐severe BPD in the northern Finnish population. When all the populations were combined, SNP rs11104948 was significantly associated with BPD. Kit ligand concentration in umbilical cord blood of infants born very preterm was an independent risk factor of BPD. Conclusions: We show that KITLG polymorphisms are associated with susceptibility to moderate‐to‐severe BPD. In addition, higher Kit ligand concentrations were observed in infants that subsequently developed BPD. These results support the possibility that KITLG gene is involved in predisposition to BPD. Pediatr Pulmonol. 2015; 50:260–270. © 2014 Wiley Periodicals, Inc.